A second polymorph of β-arteether - T. V. Sreevidya (Acta Crystallographica Section E, 2008)
The crystal structure of the title compound, C17H28O5, reported here is a polymorph of the structure first reported by El-Feraly, Al-Yahya, Orabi, McPhail & McPhail [J. Nat. Prod. (1992). 55, 878–883]. It is a derivative of the antimalaria compound artemisinin and consists primarily of three substituted ring systems fused together. A cyclohexane ring (distorted chair conformation) fused to a tetrahydropyran group (distorted chair) is adjacent to an oxacycloheptane unit containing an endo-peroxide bridge, giving the molecule its particular three-dimensional arrangement. The crystal packing is stabilized by intermolecular C—H...O interactions between an O atom from the endo-peroxide bridge and H atoms from both the cyclohexane and seven-membered oxacycloheptane fused rings, as well as between an O atom and H atom from adjacent tetrahydropyran rings. The two polymorphs have the same space group and similar cell parameters for the a and b axes, but significantly different values for the c axis.